2005
DOI: 10.1002/pssc.200460812
|View full text |Cite
|
Sign up to set email alerts
|

Microwave detection using Josephson junction arrays integrated in a resonator

Abstract: The possibilities and physical mechanisms of detection of microwave X-and Ka-band radiation by hightemperature superconducting (HTS) YBa 2 Cu 3 O 7-0.05 (YBCO) bicrystalline Josephson junctions (JJ) embedded in a surface wave resonator (SWR) are considered. Microwave detection was investigated experimentally by using a linear Josephson junction array (JJA) embedded in the SWR. Measurements were carried out starting from the critical temperature of HTS film (T = 92 K), down to the liquid nitrogen level (T = 77 … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
5
0

Year Published

2008
2008
2021
2021

Publication Types

Select...
5
2
1

Relationship

0
8

Authors

Journals

citations
Cited by 8 publications
(5 citation statements)
references
References 5 publications
0
5
0
Order By: Relevance
“…Note that just such SEMWRs on the basis of a conducting film deposited onto a dielectric substrate are used in practice. For the efficient excitation of oscillations in the SEMWR, the latter is mounted inside a rectangular waveguide [6][7][8][9][10][11][12][13].…”
Section: Surface Magnon-plasmon-polaritons In the Real Ferromagnetic mentioning
confidence: 99%
See 1 more Smart Citation
“…Note that just such SEMWRs on the basis of a conducting film deposited onto a dielectric substrate are used in practice. For the efficient excitation of oscillations in the SEMWR, the latter is mounted inside a rectangular waveguide [6][7][8][9][10][11][12][13].…”
Section: Surface Magnon-plasmon-polaritons In the Real Ferromagnetic mentioning
confidence: 99%
“…is the relative dielectric permittivity of the medium: = ( ) for the real metal, = for the insulator, and → −∞ √ −1 for the ideal metal quency interval [6,7]. This system turned out convenient for developing various superconducting devices with Josephson junctions [8][9][10][11] (see also recent reviews [12,13]). The theoretical prediction of surface plasmons [14], the quasiparticles that describe collective oscillations of the electron density near the conducting-medium boundary, became a powerful impetus for intensifying the SEMW studies.…”
Section: Introductionmentioning
confidence: 99%
“…Using this concept, G.A. Melkov and A.M. Klushin with coauthors were able to develop and create microwave devices with up to 450 synchronized bicrystal Josephson junctions, to obtain the synchronous generation from ∼200 junctions, and to create SEWRbased microwave signal detectors with Josephson junction arrays [20][21][22][23][24]. These studies were carried out in the 8-mm and 3-cm wave bands for different configurations of SEWR inside a rectangular waveguide of different cross-section sizes.…”
Section: Physics and Applications Of High-temperature Superconductivitymentioning
confidence: 99%
“…In particular, it was shown that, in a below-cutoff rectangular waveguide, the spectrum of SEWR natural oscillations is substantially rarefied, which can be used for the creation of more efficient microwave devices [25,26]. The obtained results were summarized in [23,24,27].…”
Section: Physics and Applications Of High-temperature Superconductivitymentioning
confidence: 99%
“…In the works by G.A. Melkov et al written since 2000, it was proposed to use SEW resonators for measuring the surface impedances of high-temperature superconductors and for studying the Josephson junction arrays [9][10][11][12][13].…”
Section: Introductionmentioning
confidence: 99%